Herrmann, The Arming Of Europe And The Making Of The First World War - Van Hartesveldt, Fred (Teaching History: A Journal of Methods, 1998)
Even a freshman student of European history can make a list of crises that led up to World War I, including the two Moroccan confrontations, the annexation of Bosnia and Herzegovina, and the Balkan Wars. To read the Table of Contents in David Herrmann's new book one might think that he had done no more than trace this familiar pattern as so many have in the past. Herrmann has, however, done much more.